0589 Listening to the Patient Voice in Sleep Apnea: Daytime Functioning and Experience with Therapy. (12th April 2019) - McCleary, Kimberly; Amdur, Justine; Amdur, Adam; Deering, Sean; Stepnowsky, Carl J
Abstract: Introduction: Understanding the patient voice and experience is an integral part of clinical care. The American Sleep Apnea Association organized and hosted a Patient-Focused Medical Product Development (PFMPD) meeting for the FDA in June 2018. The PFMPD meeting was the first of its kind, focused on medical products in addition to medications. Prior to the PFMPD, similar Patient-Focused Drug Development (PFDD) meetings were held by the FDA beginning in 2012 as a forum for patient communities about their experiences living with their respective conditions and the treatments they are using. Methods: A national survey was conducted. It was comprised of 32-items that were a combination of multiple choice and open-text fields. Sections included diagnosis, symptoms, impact of sleep apnea on daily living, treatments and impact of treatments. The survey was developed as a "fit-for-purpose" instrument for use in conjunction with the FDA's PFDD initiative and was therefore informed by the focus of past PFDD meeting surveys and related medical literature. It was tested and refined by project staff and in a group of patients. It took an average of 17 minutes to complete. The survey was widely publicized, sent to email lists and promoted within social media. All responses were anonymous. Results: The survey was available for completion between April and August 2018 and attracted a total of 5, 630 responses, 85% of whom were sleep apnea patients and 14% were family or friends of a patient. 57% of respondents were female and 85% were diagnosed by a physician. 34% of respondents on CPAP continued to report moderate to severe daytime symptoms. 53% identified potential long-term consequences of OSA on health and lifespan as their top concern. 70% reported using CPAP, and of those, 82% reported using it 7 nights per week and 6.2 hours per night. Conclusion: The PFMPD survey conducted by the ASAA is a rich source of the sleep apnea patient's experience encompassing recognition, diagnosis, symptoms, and treatment. Support (If Any): The FDA AWAKE meeting was hosted by the American Sleep Apnea Association.